The Problems of the World of Education in the Middle of the Covid-19 Pandemic - Beby Masitho Batubara (Budapest International Research and Critics University, 2021)
Indonesia is the number one country with the highest number of Covid patients in Central Asia. This has an impact on various sectors including the education sector. In Indonesia, approximately 45 million students in Indonesia or it can be said that 3% of the total data globally, students who cannot take part in learning, the government issued a learning process policy in the midst of a pandemic, this policy determines the learning process which is usually carried out face-to-face, changes be learning online. This research uses a qualitative descriptive approach, with the type of library research, which is the collection of data related to the object of research in the form of literature or studying and deepening the literature literature books, reports and scientific journals, research results and other sources. The obstacles faced in implementing this learning method, namely the unpreparedness of students in the online teaching and learning process,Several studies have stated that not all of the teaching staff in Indonesia in various regions are equalized in carrying out the learning process online based on quality, competency in the use of communication and technology). Not only that, the weak education of the elderly to accompany students in using online media and not supported by facilities to carry out online learning. Dith the provision of internet networks with requiresubstantial costs. The problems in the world of education amid the Covid-19 pandemic must be a serious concern of the central and local governments.